Spatial and temporal dynamics of nitrogen and phosphorus in reservoir catchment - Chow M.F.; Leong Y.X.; Subramaniam P. (American Institute of Physics Inc., 2023)
This study evaluates the long-term patterns of nitrogen and phosphorus in Fei-Tsui Reservoir in Northern Taiwan during the periods of 1986 to 2014. Understanding the temporal and spatial mechanisms of nutrient enrichment is essential to control water quality. Here, we assess the long-term trends of runoff and nutrient concentration (1986-2014). Mann-Kendall trend test (MKT) analysis was used to assess the significance of monotonic trends (increase and/or decrease) in runoff, weather related parameters, and nutrients. We observed that N and P at the reservoir surface water showed increasing trends from 1987 onwards and started to show signs of decrease starting from 2006 until 2014. In term of flux analysis, the N and P showed increments from February to March and decreases in April. Then, the flux increases again from April until August. It can be concluded that higher amount of rainfall influences the amount of nutrients being discharged to a water body via surface runoff. 2021 American Institute of Physics Inc.. All rights reserved.